Cyclophilin inhibition as a strategy for the treatment of human disease - Stauffer, Winston T.; Goodman, Asha Z.; Gallay, Philippe A. (Frontiers in Pharmacology, 2024)
Cyclophilins (Cyps), characterized as peptidyl-prolyl cis-trans isomerases (PPIases), are highly conserved and ubiquitous, playing a crucial role in protein folding and cellular signaling. This review summarizes the biochemical pathways mediated by Cyps, including their involvement in pathological states such as viral replication, inflammation, and cancer progression, to underscore the therapeutic potential of Cyp inhibition. The exploration of Cyp inhibitors (CypI) in this review, particularly non-immunosuppressive cyclosporine A (CsA) derivatives, highlights their significance as therapeutic agents. The structural and functional nuances of CsA derivatives are examined, including their efficacy, mechanism of action, and the balance between therapeutic benefits and off-target effects. The landscape of CypI is evaluated to emphasize the clinical need for targeted approaches to exploit the complex biology of Cyps and to propose future directions for research that may enhance the utility of non-immunosuppressive CsA derivatives in treating diseases where Cyps play a key pathological role.